TYPES OF PRIMARY AND SECONDARY PREDICATION: A LINGUISTIC ANALYSIS - Teshaboyeva Nafisa Zubaydulla qizi; Xidirova Dilnoza Nurali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Primary and secondary predication are fundamental concepts in the study of syntax and sentence structure. Primary predication refers to the core, obligatory relationship within a clause, typically between a subject and a verb. Secondary predication, on the other hand, involves an additional, often optional, descriptive layer that modifies or provides information about the subject, object, or another aspect of the sentence. This article examines the distinctions and types of primary and secondary predication, providing examples and discussing their syntactic and semantic roles. By understanding these forms of predication, linguists can gain insights into sentence structure, meaning, and cross-linguistic variation.